Legal Protection Due to the Non-Competition Clause in Franchise Contract - Miftahul Rosyadi; Djunaedi Djunaedi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This study aims to: 1) Knowing and analyzing the legal protection due to the non-competition clause in the franchise agreement, 2) Knowing and analyzing the non-competition clause that has fulfilled the elements of article 1320 of the Civil Code regarding the terms of the validity of the agreement, 3) Knowing the example of the deed franchise agreement. The research method used in this study is a normative juridical method with secondary data sources. The research specification used is descriptive analysis. Researchers used normative research specifications with secondary data sources. The secondary data used by the researcher was collected by conducting a literature study by reviewing, analyzing and then processing it into a descriptive narrative so that it was easy to read. The data analysis method used by the researcher consists of the stages that the secondary data obtained will be used for descriptive-qualitative analysis. Based on the research, it is concluded that the legal protection due to the non-competition clause in the franchise agreement of Serba Wenak Restaurant is explained that in Article 13 of the draft franchise contract regarding trade secrets that franchisees are required to keep the system, management and methods of restaurant management secret from the franchisor during their tenure. The term of the agreement lasts or has expired. One of the characteristics of the Versatile Restaurant franchise is that there must be a written agreement (contract), In this case, the Serba Wenak Restaurant franchise agreement is stated in the deed of agreement that has been agreed upon by the franchisor, represented by the company director, Mr. Drs. M. Adung Darmadung with the franchisee, Mrs. Leni Marleni.